2018
DOI: 10.1515/jpm-2016-0373
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen saturation trends in normal healthy term newborns: normal vaginal delivery vs. elective cesarean section

Abstract: Our study defines normal SpO2 levels in healthy term newborns in the first 30 min of life born by NVD and elective CS. Babies born by NVD had significantly higher SpO2 levels and attained SpO2 >90% faster than those born by elective CS. Maternal Hb, birth weight and Apgar at 10 min were significant factors affecting SpO2 levels of newborns at 10 min of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 17 publications
1
3
2
1
Order By: Relevance
“…The mean post-ductal SPO2 and preductal SPO2 values of our study population were almost the same (95.8% and 96.0% respectively). Nevertheless, the mean SPO2 value of our study population was lower than the 97.4% mean SPO2 value reported by another study,24 and this can be explained by the high altitude location of our study setting.…”
Section: Discussioncontrasting
confidence: 91%
“…The mean post-ductal SPO2 and preductal SPO2 values of our study population were almost the same (95.8% and 96.0% respectively). Nevertheless, the mean SPO2 value of our study population was lower than the 97.4% mean SPO2 value reported by another study,24 and this can be explained by the high altitude location of our study setting.…”
Section: Discussioncontrasting
confidence: 91%
“…In the present study we found mean SpO2 at 10 min after birth in NVD was 94.96±1.44 and 93.78±1.62 <0.001, while Bhargava et al (2018), illustrated in their study that ; Mean SpO2 at 10 min after birth in NVD was 91.8% (±5.1) and 89.9% (±4.48) in CS (P = 0.005) respectively. In the current study; O2 saturation for included newborns delivered vaginally is higher than those delivered by CS over time, this agreed with Bhargava et al (2018), studied babies born by normal vaginal delivery had significantly higher SpO2 levels and attained SpO2 >90% faster than those born by elective CS as it has been speculated that in vaginally delivered neonates, the catecholamine surge is significantly higher compared to neonates delivered by CS, which may be the reason for higher levels of SpO2 after vaginal delivery.…”
Section: Discussionsupporting
confidence: 49%
“…Similar findings were found in a study by Rashi Bhargava et al, who discovered that the median time for SpO 2 to reach >90% in SVD and LSCS was 9.13 min and 12.31 min, respectively ( p 0.001). 11…”
Section: Discussionmentioning
confidence: 99%